Testing of a full-scale mass timber diaphragm - Kode, Anirudh, author; van de Lindt, John W., advisor; Mahmoud, Hussam, committee member; Shuler, Scott, committee member (Colorado State University. Libraries, 2018)
Cross Laminated Timber (CLT) has only recently garnered attention as a new building material in the United States. Despite being introduced in Europe nearly 20 years ago, CLT is still not used widely in North America. One primarily reason is because CLT is not yet recognized as a structural system for seismically active regions of the U.S. One sub-assembly that has not been fully investigated are horizontal diaphragms for floors, roofs, or bridge decks. This thesis aims to test a single large scale CLT cantilever diaphragm subjected to a simulated seismic load. Data was collected and the behavior of the diaphragm documented to help begin to reduce this dearth of CLT data in the U.S. This data will also assist in refining CLT diaphragm design procedures that have recently been developed. Ten CLT panels were used to build the diaphragm, which was setup as a cantilever beam according to ASTM specifications. A 110-kip actuator was used to apply a concentrated load at one end of the diaphragm while a steel base serving as a fixed boundary condition was at the other end. The CUREE test protocol with a reference displacement of 75.6 mm (3 inches) was applied to the floor diaphragm specimen, which included a number of string potentiometers to collect displacement data. The diaphragm behaved in a predictable manner and the connectors failed in tension first even with a chord designed per the National Design Specification (NDS) for wood. Then the CLT panels separated resulting in a total failure. This data set will be made available to those working on CLT diaphragm provisions for refinement of on-going revisions.
Keywords: diaphragm; cross laminated timber; mass timber